2017
DOI: 10.3390/su9101830
|View full text |Cite
|
Sign up to set email alerts
|

Addressing “Wicked Problems” through Governance for Sustainable Development—A Comparative Analysis of National Mineral Policy Approaches in the European Union

Abstract: Abstract:The achievement of sustainable development (SD) in the supply of minerals poses significant challenges for governments and public administrations on all levels, because ensuring a sustainable supply constitutes a "wicked" problem that has no clear set of alternative solutions due to its social, institutional and scientific complexities. This paper explores how this problem is addressed through "governance for SD" principles (horizontal policy integration and participation; long-term vision/short-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 70 publications
(95 reference statements)
0
13
0
2
Order By: Relevance
“…Achieving resource security is a key question for the economic development and objectives of the EU climate policy, including the EU Green Deal Communication [8], adopted on 11 December 2019. The European Union aspires to reduce the import dependency of raw materials that are critical for its industries by, among other goals, improving access to and utilization of their existing primary resources and increasing recycling activities [9][10][11][12][13]. Simultaneously, a strong focus has been put on the key elements of sustainable development-environmental, economic, and societal development [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Achieving resource security is a key question for the economic development and objectives of the EU climate policy, including the EU Green Deal Communication [8], adopted on 11 December 2019. The European Union aspires to reduce the import dependency of raw materials that are critical for its industries by, among other goals, improving access to and utilization of their existing primary resources and increasing recycling activities [9][10][11][12][13]. Simultaneously, a strong focus has been put on the key elements of sustainable development-environmental, economic, and societal development [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Many of today's most pressing societal challenges, including terrorism and homeland security, food waste, climate change, involuntary migration, poverty alleviation and underemployment, are cross‐cutting the boundaries of established jurisdictions, governance levels, and policy domains (Candel & Biesbroek, ). These types of multifaceted problems, variously defined as messy problems with clumsy solutions (Endl, ), pose a major challenge to scholars because they involve more than one PS and, indeed, require NGAs that call for multiple policy tools, coalitions of actors and interests, and new modes of interaction. What is new about this new governance is “the values that governance proponents advocate, … values which include … adaptability, integrative solutions that transcend the traditional silos of government” (Tollesfon et al, , p. 5).…”
Section: Governance Beyond Pss: the Analytical Frameworkmentioning
confidence: 99%
“…In a recent study of Corporate Social Responsibility (CSR) practices in the Portuguese mining industry, Gaspar Alves and Mendes Rodrigues (2017), for example, noted "results suggest that CSR practices are not integrated in the management control system, are not part of a long-term environment strategy, and only reflect compliance with Portuguese legislation." Further, Endl (2017) has observed that "the achievement of sustainable development (SD) in the supply of minerals poses significant challenges for governments and public administrations on all levels." Around the turn of the millennium, the executive report on the Mining, Minerals and Sustainable Development (MMSD) Project, initiated by nine of the world's leading mining companies, examined "the role of the minerals sector in contributing to sustainable development, and how that contribution could be increased" (International Institute for Environment and Development, 2002).…”
Section: Introductionmentioning
confidence: 99%